Obstacles to the Participation of University of Jordan Students in Party Work and Proposals to Solve Them - AL-Awamrah, Abdel-salam Fahad (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to identify the obstacles affecting the participation of University of Jordan students in party work and to present proposals for resolving these issues. It highlights the importance of student participation in party work, especially in light of developments in Jordan following the 2021 Political Modernization Committee and amendments to electoral and party laws. Methods: The study used a descriptive survey method, employing a questionnaire as a data collection tool. The population consisted of all 54,189 students at the University of Jordan during the second semester of the 2022-2023 academic year. A stratified random sampling method was used, resulting in a sample of 400 students. Results: The study found a high level of agreement among students on the impact of obstacles related to the nature of party work and their own perceptions of political parties on their participation. It identified proposals to enhance student participation, including aligning programs with societal developments in Jordan. Attitudes varied by gender, with females showing more positive attitudes, and by academic year, favoring third- and fourth-year students over second-year students. No significant differences were found related to the faculty. Conclusion: The study identified obstacles to University of Jordan students’ participation in party work and their relationship to certain demographic variables, offering proposals to mitigate these obstacles. It recommends that Jordanian political parties develop programs specifically aimed at university students to meet their needs and raise their awareness of the importance of participating in party work.